Synthesis and characterization of some 2-sulphanyl benzimidazole derivatives and study of effect as corrosion inhibitors for carbon steel in sulfuric acid solution - Al-Majidi, Suaad; Al-Jeilawi, Uday; Al-Saadie, Khulood (Iraqi Journal of Science, 2024)
This research involves the synthesis of some sulphanyl benzimidazole derivatives (Ia-c), which were prepared from reaction of 2-mercaptobenzimidazole substituted benzyl halide, and structures were identified by spectral methods[FTIR, 1H-NMR and 13C-NMR].These compounds were investigated as corrosion inhibitors for carbon steel in 1M H2SO4 solution using weight loss, potentiostatic polarization methods; obtained results showed that the sulphanyl benzimidazole derivatives retard both cathodic and anodic reactions in acidic media, by virtue of adsorption on the carbon steel surface. This adsorption obeyed Langmuir’s adsorption isotherm. The inhibition efficiency of (Ia-c) ranging between (65-92) %. By using different Ib derivative concentration and temperature, the carbon steel corrosion rate was decreased with increasing Ib concentration and the highest inhibition efficiency reach to 92.8% by using 4.6×10-4 M Ib concentration at 308 K,the inhibition efficiency increases with increasing temperature ranging(308-338)K